Immersive dance and virtual realities. Issue 2 (1st December 2017) - Birringer, Johannes
This article offers a reflection on the mixed reality experience and a layered approach, devised for the theatrical environment of kimosphere no. 4/Horlà, viewed as an expanded, multi-sensorial sense of playful immersion. This research on new choreographic architectures was conducted with colleagues in the DAP-Lab, developing further our investigations of dance and wearable design. I question the role of the virtual and of wearable virtual reality (VR) headsets within the metakimosphere series and the physical theatre/dance/VR installations that I have created. I also briefly discuss the critical importance and historical context of the ritual-communal aspect of immersion and participatory art.